Network alarm reporting system - Muhammad Al-Hafidzi, Mohammad Salleh (2005)
Traditionally, network management activities, such as fault management have been performed with direct human involvement. However,these activities are becoming more demanding and complex due to increasing size of networks in information technology today. For that reason, it is becoming necessary to automate network management activities. In KUKTEM network environment, the notification of a network failure in KUKTEM has not reached the demanding of higher technology yet.Network administrators acknowledge the network failure within the working hour only.The problem is they do not acknowledge network failure which occurred out of working hour. So,they are wasting time of delaying fixing network problems. Advance concept in Network Alarm Reporting System (NARS) can play an important role in the network problem solving that is employed in fault management.The successful phases indicated in this system have been successfully applied to the network management system. NARS provide a good solution to overcome the network alarm in KUKTEM.The Continuous monitoring process from NARS will increase the quality of network management skills.The verification of network failure and notification report is an efficient way to manage network successfully.In the notification process, NARS provide reliable and fast services by applying Short Message Services as a medium of delivering report.